Workplace Compassion, Emotional Intelligence, and Positive Work Climate: The Mediating Role of Social Support among Vocational School Teachers - Yeni Rohaeni; Dedi Muhammad Siddiq; Fadiya Dina Hanifa; James Tembo; Nur Haslina (Lembaga Teewan Journal Solutions, 2026)
This study examines whether workplace compassion and emotional intelligence contribute to the development of a positive work climate among teachers in private schools in Cirebon, Indonesia, and whether workplace social support mediates these relationships. A cross-sectional survey was conducted using a multistage cluster sampling technique, resulting in 239 valid responses. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both workplace compassion and emotional intelligence are positively associated with workplace social support and a positive work climate. Workplace social support is also positively related to a positive work climate and serves as an explanatory pathway linking emotional intelligence to the work climate. However, the indirect effect of workplace compassion through workplace social support appears weaker and should be interpreted with caution. These results highlight the importance of fostering compassionate interactions, strengthening emotional competencies, and promoting structured peer support practices in order to cultivate a more supportive and psychologically safe school work environment.